Patient co‐payments and use of prescription medicines - Evan Doran; Jane Robertson; Isobel Rolfe; David Henry (Elsevier, 2004)
Abstract Objective: To investigate how prescription co‐payments influence the medicine use of Australian patients. Methods: Two surveys and an in‐depth interview study were conducted in the Newcastle/Hunter region of New South Wales (NSW). A community‐based survey explored how often prescription cost posed a barrier to prescription use. A general practice patient survey investigated the impact of prescription cost on the timing of medical consultations and prescription collection. Quantitative data were summarised using descriptive statistics; associations between household characteristics and outcomes were explored using odds ratios and chi square analysis. In‐depth interviews were conducted to explore the role of prescription cost in medicine use. The interview data were qualitatively analysed for relevant themes using 'grounded theory'. Results: 420 of 950 households (44%) participated in the community survey: 110 (26%) reported delaying visiting a GP, 85 (20%) not buying all of their prescription medicines and 77 (18%) not refilling a prescription because of cost. Sixty‐two (15%) households reported significant difficulties with prescription costs. Households with children had twice the odds of reporting significant difficulties than those without (OR = 2.0, 95% CI 1.2-3.5). Of the 442 (43%) GP patients who participated, 25 (6%) patients reported prescription cost as the reason for delaying their visit. Of the 291 patients who received a prescription, 26 (9%) patients reported cost as the reason for not collecting some or all of their prescriptions. Implications: Given the wide variation in patients' capacity to manage increased out‐of‐pocket costs, co‐payments may add to patients' burden and place a potential barrier to safe and timely prescription use.